2002
DOI: 10.1046/j.1365-2141.2002.03608.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction and characterization of cutaneous lymphocyte antigen on natural killer cells

Abstract: Summary. Cutaneous lymphocyte antigen (CLA) has been reported to be expressed mainly by memory/effector T lymphocytes infiltrating inflammatory skin lesions and cutaneous T-cell lymphoma. It has been suggested that CLA is a specific homing receptor, facilitating the T-cell migration into skin lesions, and also an indicator of the skinhoming T-cell subset. In the present study, we investigated the expression of CLA in natural killer (NK) cells defined phenotypically as surface CD3 -and CD56 + cells in periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 41 publications
0
16
1
1
Order By: Relevance
“…22 Petrella et al 7 studied CLA/CD162 and found it to be positive in 90% of BPDCN and 78% of MS cases, suggesting the lack of specificity of this marker in distinguishing MS and BPDCN. In contrast, CLA/CD162 was positive in 3/9 (33%) BPDCN cases and in 0/11 (0%) cases of MS in our study.…”
Section: Discussionmentioning
confidence: 99%
“…22 Petrella et al 7 studied CLA/CD162 and found it to be positive in 90% of BPDCN and 78% of MS cases, suggesting the lack of specificity of this marker in distinguishing MS and BPDCN. In contrast, CLA/CD162 was positive in 3/9 (33%) BPDCN cases and in 0/11 (0%) cases of MS in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Stacey et al 28 showed that the pretreatment of donor lymphocytes with neuraminidase decreases the incidence of aGVHD in murine models. This study is indirect evidence suggesting the involvement of the murine counterpart of CLA in the systemic aGVHD reaction as CLA is a sialylated 12,14 It was also shown that Th1 T cells expressing skin homing receptors can migrate to the intestinal laminapropria, and are associated with inflammation in the intestine. 29 Further, the CLA þ T cells that emerge after allo-SCT express high levels of CCR4 and CCR6, which is comparable to that of the normal donors.…”
Section: Discussionmentioning
confidence: 98%
“…A total of 1 Â 10 7 PBMCs obtained from normal volunteers were cultured and stimulated with 1 mg/ml PHA (Sigma), 100 U/ml rIL-2 (Shionogi and Co. Ltd., Osaka, Japan) and 50 ng/ml rIL-12, (Pepro Tech Inc., Rocky Hill, NJ, USA) for 5 days as reported previously. 14,15 The whole nonadherent cells were collected for analysis of CLA expression using a FACScan flow cytometer. Activated cells increased their size and the Surface-marker analysis of CLA þ T cells after allo-SCT To determine the characteristics of CLA þ T cells in PB, we obtained lymphocytes from the normal donors (n ¼ 6) and the patients at 2-4 (n ¼ 10) and 12-14 weeks (n ¼ 7), after allo-SCT.…”
Section: Culture Of Peripheral Blood Lymphocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…L'aspect histologique n'est pas spé cifique de la maladie. La prolifé ration est composé e de cellules de taille moyenne, assez monomorphes, et le diagnostic é voqué est celui d'un lymphome B ou T, d'une localisation cutané e d'une leucé mie myé loïde ou d'un sarcome granulomateux [8,13]. La cytochimie retrouve toujours les MPO et esté -rases né gatives [3].…”
Section: Discussionunclassified